Convergent Total Synthesis of Asimicin via Decarbonylative Radical Dimerization. Issue 71 (20th November 2018) - Kawamata, Takahiro; Yamaguchi, Akinori; Nagatomo, Masanori; Inoue, Masayuki
Abstract: Asimicin (1 ) exhibits potent antitumor activity and comprises a central C2 ‐symmetric bis‐tetrahydrofuran and two aliphatic side‐chains, one of which terminates with ( S )‐methyl‐2(5 H )‐furanone. This work reports a convergent total synthesis of 1 in 17 steps from d ‐gulose derivative 4 . Decarbonylative radical‐radial homo‐coupling of α‐alkoxyacyl telluride 12 a efficiently produced the C2 ‐symmetric core 3‐ SS, which was transformed into 1 through stepwise attachment of the two side‐chains and functional group manipulations. Abstract : A convergent total synthesis of the potent antitumor agent asimicin in 17 steps from a d ‐gulose derivative is reported. Decarbonylative radical‐radial homo‐coupling of α‐alkoxyacyl telluride efficiently produced the central C2 ‐symmetric bis‐tetrahydrofuran substructure, which was transformed into asimicin through stepwise attachment of the two aliphatic side‐chains.